Austenitic stainless steel welding materials

JP7633507B2Active Publication Date: 2025-02-20NIPPON STEEL CORPORATION
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021059466
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-02-20
Estimated Expiration
2041-03-31

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、高強度と高靱性とを確保しつつ、優れた耐水素脆化特性を有するオーステナイト系ステンレス鋼溶接材料が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633507000001
    Figure 0007633507000001
  • Figure 0007633507000002
    Figure 0007633507000002
Patent Text Reader

Abstract

To provide an austenitic stainless steel weld material having excellent hydrogen embrittlement resistance while ensuring high strength and high toughness.SOLUTION: An austenitic stainless steel weld material has a chemical composition consisting of, in mass%, C: 0.030% or less, Si: 0.10-0.45%, Mn: 2.00-3.00%, P: 0.030% or less, S: 0.020% or less, Ni: 12.0-14.0%, Cr: 22.0-26.0%, Mo: 2.0-3.5%, Al: less than 0.050%, N: 0.20-0.50%, O: 0.020% or less, Nb: 0-0.50%, V: 0-0.50%, with the balance being Fe and impurities, satisfying following formulae (1)-(3). Ni+0.7Cr+Mo+Mn-0.3Si+13C+8N≥35.0 (1), 0.13C+0.05Si-0.02Mn-0.05Cr+0.01Ni-0.01Mo+0.15N≤-1.00 (2), and 30C+30N+0.5Mn+1.8Ni-1.5Si-1.5Cr-Mo≥-10.0 (3).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an austenitic stainless steel welding material. [Background technology]

[0002] In recent years, there has been active research and development into transportation equipment that uses hydrogen as energy, and into the practical application of hydrogen stations that supply hydrogen. In order to put these into practical use, it is urgent to prepare an environment in which hydrogen gas can be stored and used at high pressure, and the development and application of high-strength materials with a tensile strength of 800 MPa or more is being investigated.

[0003] WO 2013 / 5570 describes a welded joint that can achieve high strength without post-weld heat treatment by increasing the N content of the weld metal through controlling the N content of the welding material, the shielding gas during welding, the molten pool area, etc. JP 2015-6678 A describes a method for producing a high-strength welded joint without using welding material.

[0004] JP 2019-63868 A describes a welding material for austenitic stainless steel that can achieve both high strength and excellent low-temperature toughness by adjusting the content of each element and further creating a structure that contains a predetermined amount of δ-ferrite. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO 2013 / 5570 [Patent Document 2] JP 2015-6678 A [Patent Document 3] JP 2019-63868 A Summary of the Invention [Problem to be solved by the invention]

[0006] At hydrogen stations, hydrogen gas is compressed and pressurized, then cooled and filled into vehicles, so the materials used at hydrogen stations must have the strength and toughness to be usable in high-pressure environments and at a wide range of temperatures from -50°C to 150°C, as well as excellent hydrogen embrittlement resistance. In particular, it is desirable for materials to exhibit excellent hydrogen embrittlement resistance at low temperatures, while also exhibiting high strength and high toughness.

[0007] WO 2013 / 5570 and JP 2015-6678 A are silent about low temperature toughness, and JP 2019-63868 A is silent about hydrogen embrittlement resistance at low temperatures.

[0008] An object of the present invention is to provide an austenitic stainless steel welding material that has excellent hydrogen embrittlement resistance while ensuring high strength and high toughness. [Means for solving the problem]

[0009] An austenitic stainless steel welding material according to one embodiment of the present invention is a welding material used for gas tungsten arc welding of austenitic stainless steel, and has a chemical composition, in mass%, of C: 0.030% or less, Si: 0.10 to 0.45%, Mn: 2.00 to 3.00%, P: 0.030% or less, S: 0.020% or less, Ni: 12.0 to 14.0%, Cr: 22.0 to 26.0%, Mo: 2.0 to 3.5%, Al: less than 0.050%, N: 0.20 to 0.50%, O: 0.020% or less, Nb: 0 to 0.50%, V: 0 to 0.50%, and the balance: Fe and impurities, and satisfies the following formulas (1) to (3). Ni+0.7Cr+Mo+Mn-0.3Si+13C+8N≧35.0 (1) 0.13C+0.05Si-0.02Mn-0.05Cr+0.01Ni-0.01Mo+0.15N≦-1.00 (2) 30C+30N+0.5Mn+1.8Ni-1.5Si-1.5Cr-Mo≧-10.0 (3) The name of each element in the formula is substituted with the content of the corresponding element in mass%. Effect of the Invention

[0010] According to the present invention, it is possible to obtain an austenitic stainless steel welding material that has excellent hydrogen embrittlement resistance while ensuring high strength and high toughness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present inventors have conducted various studies to solve the above problems. The present inventors have focused on Ni, Cr, Mo, Mn, Si, C, and N, and have found that by adjusting the contents of these elements to satisfy the following formulas (1) to (3), it is possible to obtain an austenitic stainless steel welding material that has excellent hydrogen embrittlement resistance while ensuring high strength and high toughness. Ni+0.7Cr+Mo+Mn-0.3Si+13C+8N≧35.0 (1) 0.13C+0.05Si-0.02Mn-0.05Cr+0.01Ni-0.01Mo+0.15N≦-1.00 (2) 30C+30N+0.5Mn+1.8Ni-1.5Si-1.5Cr-Mo≧-10.0 (3)

[0012] Hereinafter, an austenitic stainless steel welding material according to one embodiment of the present invention will be described in detail.

[0013] [Chemical composition] The austenitic stainless steel welding material according to this embodiment has the chemical composition described below. In the following description, "%" for the content of an element means mass %.

[0014] C: 0.030% or less Carbon (C) stabilizes austenite. This effect can be obtained even if even a small amount of C is contained. On the other hand, if the C content is too high, carbides are precipitated and the toughness is reduced. Therefore, the C content is 0.030% or less. The lower limit of the C content is preferably 0.005%, and more preferably 0.008%. The upper limit of the C content is preferably 0.025%, and more preferably 0.020%.

[0015] Silicon: 0.10 to 0.45% Silicon (Si) is contained as a deoxidizing agent and has the effect of improving the corrosion resistance of steel. On the other hand, if the Si content is too high, the stability of austenite decreases and ductility decreases. Therefore, the Si content is 0.10 to 0.45%. The lower limit of the Si content is preferably 0.15%, and more preferably 0.20%. The upper limit of the Si content is preferably 0.40%, and more preferably 0.35%.

[0016] Mn: 2.00-3.00% Manganese (Mn) stabilizes austenite. If the Mn content is too low, the solubility of N decreases, and the effect of indirectly improving strength decreases. On the other hand, if the Mn content is too high, the workability of the steel decreases. Therefore, the Mn content is 2.00 to 3.00%. The lower limit of the Mn content is preferably 2.20%, and more preferably 2.30%. The upper limit of the Mn content is preferably 2.80%, and more preferably 2.70%.

[0017] P:0.030% or less Phosphorus (P) is an impurity. P reduces the toughness and weldability of steel. Therefore, the P content is 0.030% or less. The P content is preferably 0.020% or less, and more preferably 0.010% or less.

[0018] S: 0.020% or less Sulfur (S) is an impurity. S reduces the toughness and weldability of steel. Therefore, the S content is 0.020% or less. The S content is preferably 0.010% or less, and more preferably 0.005% or less.

[0019] Ni: 12.0-14.0% Nickel (Ni) is an austenite forming element and improves hydrogen embrittlement resistance and low temperature toughness. On the other hand, if the Ni content is too high, the solubility of N decreases, and the effect of indirectly improving strength decreases. Therefore, the Ni content is 12.0 to 14.0%. The lower limit of the Ni content is preferably 12.2%, and more preferably 12.5%. The upper limit of the Ni content is preferably 13.8%, and more preferably 13.5%, and more preferably 13.2%.

[0020] Cr: 22.0~26.0% Chromium (Cr) improves the corrosion resistance of steel and increases the solubility of N, thereby contributing to improving strength. On the other hand, if the Cr content is too high, the stability of austenite decreases. Therefore, the Cr content is 22.0 to 26.0%. The lower limit of the Cr content is preferably 22.5%, and more preferably 23.0%. The upper limit of the Cr content is preferably 25.5%, and more preferably 25.0%.

[0021] Mo: 2.0-3.5% Molybdenum (Mo) contributes to improving strength by increasing the solubility of N in addition to solid solution strengthening and precipitation strengthening. On the other hand, if the Mo content is too high, the stability of austenite decreases. Therefore, the Mo content is 2.0 to 3.5%. The lower limit of the Mo content is preferably 2.2%, and more preferably 2.5%. The upper limit of the Mo content is preferably 3.2%, and more preferably 3.0%.

[0022] Al: Less than 0.050% Aluminum (Al) is added as a deoxidizer. On the other hand, if the Al content is too high, a large amount of nitrides are formed, which leads to a decrease in ductility. Therefore, the Al content is less than 0.050%. The Al content is preferably 0.030% or less, and more preferably 0.010% or less. There is no need to set a lower limit for the Al content, but an extreme decrease leads to an increase in manufacturing costs. The lower limit of the Al content is preferably 0.001%, and more preferably 0.002%.

[0023] N: 0.20~0.50% Nitrogen (N) is a solid solution strengthening element and contributes to increasing the strength of steel. On the other hand, if the N content is too high, hot workability during manufacturing decreases and blowholes tend to occur during welding. Therefore, the N content is 0.20 to 0.50%. The lower limit of the N content is preferably 0.22%, and more preferably 0.25%. The upper limit of the N content is preferably 0.45%, and more preferably 0.40%.

[0024] O: 0.020% or less Oxygen (O) is an impurity. O reduces the hot workability, toughness, and ductility of steel. Therefore, the O content is 0.020% or less. The O content is preferably 0.015% or less, and more preferably 0.010% or less.

[0025] The balance of the chemical composition of the austenitic stainless steel welding material according to the present embodiment is Fe and impurities, which refer to elements that are mixed in from ores or scraps used as raw materials when industrially producing steel, or elements that are mixed in from the environment during the production process, etc.

[0026] The chemical composition of the austenitic stainless steel welding material according to this embodiment may contain one or both of Nb and V in place of a portion of Fe. Both Nb and V are optional elements. In other words, the chemical composition of the austenitic stainless steel welding material according to this embodiment may not contain one or both of Nb and V.

[0027] Nb: 0 to 0.50% Niobium (Nb) improves the strength of steel by solid solution strengthening and precipitation strengthening. This effect can be obtained even if even a small amount of Nb is contained. On the other hand, if the Nb content is too high, nitrides are excessively precipitated and the toughness is reduced. Therefore, the Nb content is 0 to 0.50%. The lower limit of the Nb content is preferably 0.01%. The upper limit of the Nb content is preferably 0.30%, and more preferably 0.20%.

[0028] V: 0~0.50% Vanadium (V) improves the strength of steel by solid solution strengthening and precipitation strengthening. This effect can be obtained even if even a small amount of V is contained. On the other hand, if the V content is too high, nitrides are excessively precipitated and the toughness is reduced. Therefore, the V content is 0 to 0.50%. The lower limit of the V content is preferably 0.01%, and more preferably 0.05%. The upper limit of the V content is preferably 0.30%, and more preferably 0.20%.

[0029] [Regarding formulas (1) to (3)] The chemical composition of the austenitic stainless steel welding material according to this embodiment satisfies the following formulas (1) to (3). Ni+0.7Cr+Mo+Mn-0.3Si+13C+8N≧35.0 (1) 0.13C+0.05Si-0.02Mn-0.05Cr+0.01Ni-0.01Mo+0.15N≦-1.00 (2) 30C+30N+0.5Mn+1.8Ni-1.5Si-1.5Cr-Mo≧-10.0 (3) The name of each element in the formula is substituted with the content of the corresponding element in mass%.

[0030] Formula (1) is a condition for obtaining excellent hydrogen embrittlement resistance. The left side of formula (1) is an index of austenite stability. The larger the value of the left side of formula (1), the more stable the austenite is, and the less likely it is that deformation-induced martensite will be formed. This can improve the hydrogen embrittlement resistance of the austenitic stainless steel welding material. The value of the left side of formula (1) is preferably 35.5 or more, more preferably 36.0 or more, and even more preferably 36.5 or more.

[0031] Formula (2) is a condition for obtaining high strength. The left side of formula (2) is an index of N activity. The smaller the value of the left side of formula (2), the smaller the activity of N and the higher the solubility of N in the steel. The higher the solubility of N in the steel, the stronger the strength of the steel is due to solid solution strengthening of N. Cr, Mn, and Mo reduce the activity of N, while Ni, N, Si, and C increase the activity of N. The value of the left side of formula (2) is preferably -1.05 or less, more preferably -1.07 or less, and even more preferably -1.10 or less.

[0032] Formula (3) is a condition for obtaining high toughness. The left side of formula (3) is an index of suppression of ferrite formation. The larger the value of the left side of formula (3), the more the formation of ferrite is suppressed. This can improve the toughness of the austenitic stainless steel welding material. The value of the left side of formula (3) is preferably -8.0 or more, more preferably -7.0 or more, and even more preferably -6.6 or more.

[0033] [Organization] The structure of the austenitic stainless steel welding material according to this embodiment is mainly composed of austenite phase. The structure of the austenitic stainless steel welding material according to this embodiment may contain small amounts of ferrite and other structures. The volume fraction of the austenite phase in the structure of the austenitic stainless steel welding material according to this embodiment is preferably 80% or more, and more preferably 85% or more.

[0034] [Tensile strength] The austenitic stainless steel welding material according to this embodiment preferably has a tensile strength of 800 MPa or more at room temperature, and more preferably has a tensile strength of 830 MPa or more at room temperature.

[0035] [Low temperature toughness] The austenitic stainless steel welding material according to this embodiment preferably has an impact value of 20 J or more in a Charpy impact test at −20° C. The austenitic stainless steel welding material according to this embodiment more preferably has an impact value of 25 J or more in a Charpy impact test at −20° C.

[0036] [Manufacturing method etc.] An example of a method for producing the austenitic stainless steel welding material according to the present embodiment will be described. The method for producing the austenitic stainless steel welding material is not limited to this.

[0037] Steel having the above-mentioned chemical composition is produced. For example, an electric furnace, an Ar-O2 mixed gas bottom blowing decarburization furnace (AOD furnace), a vacuum decarburization furnace (VOD furnace), etc. can be used for the production. The produced steel is cast into an ingot, and the ingot is hot worked to produce a welding material. The shape of the welding material is, for example, a rod, a wire, a block, etc.

[0038] The austenitic stainless steel welding material according to the present embodiment is used for gas tungsten arc welding of austenitic stainless steel. EXAMPLES

[0039] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0040] Ingots were prepared by melting in a laboratory the steels designated A to T having the chemical compositions shown in Table 1. The values ​​in the columns F1, F2, and F3 in Table 1 are the values ​​on the left side of formula (1), formula (2), and formula (3), respectively.

[0041] [Table 1]

[0042] The produced ingot was subjected to hot forging, hot rolling, cold rolling and heat treatment to produce a spool-shaped welding material having an outer diameter of 1.2 mm.

[0043] Using the prepared welding materials, all-weld metal test pieces were prepared. Specifically, automatic gas tungsten arc welding (GTAW) was used to perform buttering welding on the groove surface, followed by layer welding in the groove. The heat input was 8-12 kJ / cm, and the interlayer temperature was 150°C or less. No pre-weld heat treatment (preheating) or post-weld heat treatment was performed. From the prepared all-weld metal test pieces, SSRT test pieces, tensile test pieces, and Charpy impact test pieces were each taken so that the longitudinal direction of the test pieces was parallel to the weld line.

[0044] The SSRT test specimens were round bar specimens with a parallel part diameter of 3 mm. The specimens were subjected to slow strain rate tensile tests in air and in a high-pressure hydrogen environment of 85 MPa. The test temperature was -50°C. The strain rate was 3×10 -5 In the slow strain rate tensile test, the ratio of the reduction in area at break in a high pressure hydrogen environment to the reduction in area at break in air (hereinafter referred to as "relative reduction in area at break") was 80% or more, which was rated as "pass", while the relative reduction in area at break of 90% or more was rated as "excellent", and the ratio of 80% or more but less than 90% was rated as "good".

[0045] The tensile test pieces were round bar test pieces with a parallel part diameter of 6 mm. Tensile tests were performed at room temperature in the air to measure the tensile strength. In the tensile test, specimens that showed a tensile strength of 800 MPa or more were rated as passing, those with a tensile strength of 830 MPa or more were rated as "excellent," and those between 800 MPa and 830 MPa were rated as "good."

[0046] The Charpy impact test specimens were full-size 2mm V-notch test specimens in accordance with JIS Z 2242. The Charpy impact test was carried out at -20°C. In the Charpy impact test, specimens showing an impact value of 20J or more were rated as passing, those showing an impact value of 25J or more were rated as "excellent", and those showing an impact value of 20J or more but less than 25J were rated as "good".

[0047] The results of the SSRT test, tensile test, and Charpy impact test are shown in Table 2. "-" in Table 2 indicates that the corresponding test was not performed.

[0048] [Table 2]

[0049] All the weld metal test pieces made from the welding materials with symbols A to K had a relative reduction in area of ​​80% or more, a tensile strength of 800 MPa or more, and showed an impact value of 20 J or more in a Charpy impact test at -20°C.

[0050] A weld defect (blowhole) occurred in the all-deposited metal test piece made from the welding material designated L. Therefore, the SSRT test, tensile test, and Charpy impact test were not performed on the welding material designated L. It is considered that the blowhole occurred because the welding material designated L did not satisfy formula (2), and therefore N could not dissolve in the weld metal, and was ejected as nitrogen gas during welding.

[0051] The all-weld metal test piece made from the welding material designated by code M did not pass the Charpy impact test. This is believed to be because the welding material designated by code M did not satisfy formula (3).

[0052] The total weld metal specimen made from the welding material designated N did not pass the SSRT test. This is believed to be because the welding material designated N did not satisfy formula (1).

[0053] The total weld metal specimen made from the welding material designated O did not pass the SSRT test and the tensile test. This is believed to be because the welding material designated O did not satisfy formula (1) and formula (2).

[0054] The total weld metal specimens made from the welding material with code P did not pass the Charpy impact test. This is believed to be because the Cr content of the welding material with code P was too high.

[0055] The total weld metal specimen made from the welding material with code Q did not pass the tensile test. This is believed to be because the Ni content of the welding material with code Q was too high and the welding material with code Q did not satisfy formula (2).

[0056] The total weld metal specimens made from the welding material with code R did not pass the SSRT test and the Charpy impact test. This is believed to be because the Ni content of the welding material with code R was too low.

[0057] The total weld metal specimens made from the welding material with code S did not pass the SSRT test and the tensile test. This is believed to be because the welding material with code S did not satisfy formula (1) and the N content of the welding material with code S was too low.

[0058] The total weld metal specimens made from the weld material with code T did not pass the tensile test. This is believed to be because the N content of the weld material with code T was too low.

[0059] Although the embodiment of the present invention has been described above, the above-mentioned embodiment is merely an example for carrying out the present invention. Therefore, the present invention is not limited to the above-mentioned embodiment, and the above-mentioned embodiment can be appropriately modified and carried out without departing from the spirit of the present invention.

Claims

[Claim 1] A welding material used for gas tungsten arc welding of austenitic stainless steel, The chemical composition, in mass%, is C: 0.030% or less, Si: 0.10-0.45%, Mn: 2.00-3.00%, P: 0.030% or less, S: 0.020% or less, Ni: 12.0-14.0%, Cr: 22.0-26.0%, Mo: 2.0 to 3.5%, Al: less than 0.050%; N: 0.20-0.50%, O: 0.020% or less, Nb: 0 to 0.50%, V: 0 to 0.50%, The balance is Fe and impurities. An austenitic stainless steel welding material that satisfies the following formulas (1) to (3): Ni+0.7Cr+Mo+Mn-0.3Si+13C+8N≧35.0 (1) 0.13C+0.05Si-0.02Mn-0.05Cr+0.01Ni-0.01Mo+0.15N≦-1.00 (2) 30C+30N+0.5Mn+1.8Ni-1.5Si-1.5Cr-Mo≧-10.0 (3) The content of each element in the formula is substituted for the name of the corresponding element in mass %.

Citation Information

Patent Citations

  • Ultra-low temperature austenite stainless steel solid core welding wire

    CN103042316A

  • Welding material for weld cladding

    EP2737972A1

  • Austenitic stainless steel having high strength and high toughness under superlow temperature and excellent in weldability

    JP1988050449A

  • Welding material for austenitic stainless steel and welding method

    JP1995088684A

  • Welded structure and its production

    JP1997291343A